Level Control in Conical Tank Using IMC-PID Controller - Prasad, Durga; Singh, R.S. (International Hellenic University - School of Science, 2023)
An IMC-PI/PID controller with a first or second order filter in series is designed for several types of processes with time delay. The tradeoff between performance and robustness is done by adjusting the tuning parameter of the controller. The present tuning method shows better performances in terms of overshoot (OS), settling time and ITAE error index. Simulated results of various processes are compared with recently published tuning methods and it provide better response in set point change and comparable in load change. A set point weighting parameter ‘b’ is used to remove the undesirable overshoot, which is easier to select in comparison to the set point filter. The controller’s parameters are fixed in such a way that give same robustness level (maximum sensitivity Ms), by adjusting the tuning parameter. A 10% to 15% perturbation in all the parameters of process models is introduced to evaluate the robustness of the proposed tuning method. In the present study, a conical tank system is considered for the applicability of the proposed design method of PI/PID controller. The proposed tuning method is used for designing the PI controller and successfully applied to the transfer function model and process of conical tank. The simulated and experimental results are compared with two other recently published tuning techniques.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: Conical tank; IMC; ITAE; PID